Interpreting biodiversity: the avifauna of the Campos Gerais National Park (Paraná, Brazil) (Terr@ Plural, 2021)
Environmental interpretation is a tool that helps in understanding the landscapeand its elements, frequently used in protected areas (PA) to sensitize visitors. To improveenvironmental interpretation and promote bird watching in the Campos Gerais NationalPark, this paper aims to discuss the importance of interpretative means to achieve theobjectives of the PA, presenting a proposal for a panel and a folder of the present avifauna. Forthis, besides the bibliographical research and expert consulting, we carried out field visits.It is concluded that the proposed tools could improve the interpretation/identification, aswell as in the promotion of sustainable tourism potential in the conservation of birdlife.
Keywords: envirolmental interpretation; birdwatching; protected areas; ecotourism